Revitalizing The Regeneration System Of Political Parties In Building Pancasila Democracy - Luhukay, Roni Sulistyanto (JURNAL LEGALITAS, 2024)
Problems with recruitment and regeneration systems and patterns that are carried out instantly can contribute to the community's negative perception of political parties. Political parties are more likely to recruit ready-made cadres rather than cadres who have been raised and have experienced the process of party life from a difficult period to the achievement of the party's goals, resulting in recruitment patterns and patterns of Cadre of Political Party Members who are less loyal and competent. This study employs normative juridical research. This study discovered that the decline in the quality of political party regeneration is inextricably linked to political parties' unclear ideology, problematic political party funding, and democracy that has been hijacked from the start because political dowries are viewed as political investments that must eventually be paid for with policies that are not beneficial to certain groups as capital providers. The revitalization of the Political Party Cadre System had implications for the development of the democracy of Pancasila, which includes the development of the constitutional life order as well as all aspects of life, including the establishment of economic, social, political, cultural, defense, security, and legal systems. An adequate political party cadre system includes political parties with a clear ideology, state direction in politics, an obvious curriculum and cadre, trainers, guidelines, and, finally, a system for tracking and assessing progress. Aside from that, the implications of the cadre of members of the candidate pair have 4 (four) impacts in the cadre system: the first is that party cadres have sufficient competence to carry out their duties; the second has devotion while being a party cadre and a good track record while active in the political party; the third has achievements, dedication, discipline, loyalty, and irreproachable (PD2LT); and the fourth meets the provisions required by law. The novelty of this research lies in the quality of democracy which is only placed on the electoral candidate pair or the power of the candidate pair's political dowry to be able to buy the electorate, but the quality of democracy needs to be placed on the ideology of the political party, the state's direction in politics, clear curriculum and cadres, and trainers as such. So political parties are expected to represent society in making choices in line with the development of Pancasila democracy